2015
DOI: 10.1515/revneuro-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness, awareness of insight and neural mechanisms of schizophrenia

Abstract: AbstractAccording to recent research, disturbances of self-awareness and conscious experience have a critical role in the pathophysiology of schizophrenia, and in this context, schizophrenia is currently understood as a disorder characterized by distortions of acts of awareness, self-consciousness, and self-monitoring. Together, these studies suggest that the processes of disrupted awareness and conscious disintegration in schizophrenia might be related and represented by simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 139 publications
(217 reference statements)
1
6
0
Order By: Relevance
“…It is a failure to make consensually valid sense of complex and potentially traumatic experiences. This view is consistent with studies of firstperson experience of psychosis, which demonstrate that insight is most significant to persons with psychosis when it helps them make sense or meaning of life events in a narratized manner [191][192][193][194] .…”
Section: Summary and Future Directionssupporting
confidence: 84%
“…It is a failure to make consensually valid sense of complex and potentially traumatic experiences. This view is consistent with studies of firstperson experience of psychosis, which demonstrate that insight is most significant to persons with psychosis when it helps them make sense or meaning of life events in a narratized manner [191][192][193][194] .…”
Section: Summary and Future Directionssupporting
confidence: 84%
“…What becomes split in dissociation phenomena: the personality, the identity or some psychic functions like cognition and affectivity? (4)(5)(6). In the light of current evidence for overlapping symptoms between schizophrenia and complex PTSD, especially when traumatic events like sexual abuse, child maltreatment or neglect occur in the childhood, this question links to the nature of "splitting of the mind" that is at the basis of the concept of "schizophrenia", as was proposed by Egon Bleuler in 1911 (7,8).…”
Section: Zusammenfassungmentioning
confidence: 99%
“…In social situations these difficulties can lead to confusion, paranoid interpretations and inappropriate reactions that can make it difficult for these individuals to forge and sustain friendships or social relationships (Mazurek 2010; Harley 2012). They can also show deficits in awareness of self and others and in the ability to make an accurate evaluation of reality, of the emotional content of social scenes/situations and of their inner states (Sasson 2007; Williams 2010; Touskova 2015). Nevertheless, studies have also found different patterns of social cognition abnormalities between the groups and it has even been suggested that these disorders exhibit diametric deficits, with theory of mind being underdeveloped in autism spectrum conditions and overdeveloped in psychosis (Crespi 2008; Bara 2011).…”
Section: Boundaries and Overlapsmentioning
confidence: 99%